A Novel 3-Sulfinopropionyl Coenzyme A (3SP-CoA) Desulfinase from Advenella mimigardefordensis Strain DPN7(T) Acting as a Key Enzyme during Catabolism of 3,3′-Dithiodipropionic Acid Is a Member of the Acyl-CoA Dehydrogenase Superfamily - Schürmann, Marc (American Society for Microbiology, 2013)
3-Sulfinopropionyl coenzyme A (3SP-CoA) desulfinase (Acd(DPN7)) is a new desulfinase that catalyzes the sulfur abstraction from 3SP-CoA in the betaproteobacterium Advenella mimigardefordensis strain DPN7(T). During investigation of a Tn5::mob-induced mutant defective in growth on 3,3′-dithiodipropionate (DTDP) and also 3-sulfinopropionate (3SP), the transposon insertion was mapped to an open reading frame with the highest homology to an acyl-CoA dehydrogenase (Acd) from Burkholderia phenoliruptrix strain BR3459a (83% identical and 91% similar amino acids). An A. mimigardefordensis Δacd mutant was generated and verified the observed phenotype of the Tn5::mob-induced mutant. For enzymatic studies, Acd(DPN7) was heterologously expressed in Escherichia coli BL21(DE3)/pLysS by using pET23a::acd(DPN7). The purified protein is yellow and contains a noncovalently bound flavin adenine dinucleotide (FAD) cofactor, as verified by high-performance liquid chromatography–electrospray ionization mass spectrometry (HPLC-ESI-MS) analyses. Size-exclusion chromatography revealed a native molecular mass of about 173 kDa, indicating a homotetrameric structure (theoretically 179 kDa), which is in accordance with other members of the acyl-CoA dehydrogenase superfamily. In vitro assays unequivocally demonstrated that the purified enzyme converted 3SP-CoA into propionyl-CoA and sulfite (SO(3)(2−)). Kinetic studies of Acd(DPN7) revealed a V(max) of 4.19 μmol min(−1) mg(−1), an apparent K(m) of 0.013 mM, and a k(cat)/K(m) of 240.8 s(−1) mM(−1) for 3SP-CoA. However, Acd(DPN7) is unable to perform a dehydrogenation, which is the usual reaction catalyzed by members of the acyl-CoA dehydrogenase superfamily. Comparison to other known desulfinases showed a comparably high catalytic efficiency of Acd(DPN7) and indicated a novel reaction mechanism. Hence, Acd(DPN7) encodes a new desulfinase based on an acyl-CoA dehydrogenase (EC 1.3.8.x) scaffold. Concomitantly, we identified the gene product that is responsible for the final desulfination step during catabolism of 3,3′-dithiodipropionate (DTDP), a sulfur-containing precursor substrate for biosynthesis of polythioesters.